2020
DOI: 10.1002/cne.25075
|View full text |Cite
|
Sign up to set email alerts
|

Cell type‐ and layer‐specific convergence in core and shell neurons of the dorsal lateral geniculate nucleus

Abstract: Over 40 distinct types of retinal ganglion cells (RGCs) generate parallel processing pathways in the visual system. In mice, two subdivisions of the dorsal lateral geniculate nucleus (dLGN), the core and the shell, organize distinct parallel channels to transmit visual information from the retina to the primary visual cortex (V1). To investigate how the dLGN core and shell differentially integrate visual information and other modalities, we mapped synaptic input sources to each dLGN subdivision at the cell-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 128 publications
0
6
0
Order By: Relevance
“…The SMI‐32 antibody has been widely used to identify alpha RGCs and subsets of SMI‐32 + RGCs have been studied thoroughly (Bleckert et al., 2014 ; Okigawa et al., 2020 ; Schmidt et al., 2014 ; Sonoda et al., 2020 ). The RGC ON‐sustained subset, which can be labeled with SMI‐32, was reported to display a nasal‐to‐temporal gradient in cell density (Bleckert et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SMI‐32 antibody has been widely used to identify alpha RGCs and subsets of SMI‐32 + RGCs have been studied thoroughly (Bleckert et al., 2014 ; Okigawa et al., 2020 ; Schmidt et al., 2014 ; Sonoda et al., 2020 ). The RGC ON‐sustained subset, which can be labeled with SMI‐32, was reported to display a nasal‐to‐temporal gradient in cell density (Bleckert et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…SMI‐32 antibodies were first generated to label cortical neurons (Ang et al., 1991 ; Campbell & Morrison, 1989 ; Sternberger & Sternberger, 1983 ), but they are now widely used to identify all populations of alpha RGCs (Bleckert et al., 2014 ; Krieger et al., 2017 ; Okigawa et al., 2020 ; Schmidt et al., 2014 ; Sonoda et al., 2020 ). The distribution of several SMI‐32 + RGCs subsets has been studied in detail in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated a dorsoventral gradient from superficial to deeper dLGN for direction-selective retinal ganglion cell projections (Kay et al, 2011; Kim et al, 2008; Krahe et al, 2011; Martersteck et al, 2017; Okigawa et al, 2021; Rivlin-Etzion et al, 2011), as well as an overrepresentation of direction/orientation-selective responses in the dorsolateral dLGN (Piscopo et al, 2013; Román Rosón et al, 2019), in particular an overrepresentation of horizontal motion in the superficial dLGN (Marshel et al, 2012). Therefore, we asked whether dLGN interneuron specialization is also dependent on depth.…”
Section: Resultsmentioning
confidence: 98%
“…The jGCaMP7f fragment was generated using PCR with PrimeSTAR Max DNA Polymerase (TaKaRa, Shiga, Japan) on a PCR thermal cycler (TP350, TaKaRa) 57,58 . The plasmids were digested with appropriate restriction enzymes (New England BioLabs, Ipswich, MA, USA) under optimal conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Brains were post-fixed with 4% PFA in PBS, 15% sucrose in PBS overnight, and then with 30% sucrose in PBS. The brains were subjected to histological analysis 57,60 Cryoprotected samples were sectioned at a thickness of 40 µm on a freezing microtome (REM-710, Yamato Kohki). The sections were rinsed with PBS, blocked for 1−2 h in a blocking solution (50% Blocking One (Nacalai, 03953-95) in 0.1% Triton X-100/PBS (PBST)), and then incubated overnight at 4℃ with primary antibodies: rabbit anti-GFP (1:3000, Abcam, cat# ab6556), chicken anti-GFP (1:2000, Abcam, cat# ab13970), goat anti-PV (1:500, Swant, cat# PVG-213), rat anti-SOM (1:500, Millipore, cat# MAB354), and rabbit anti-VIP (1:400, ImmunoStar, cat# 20077) in 5% Blocking One/0.1% PBST.…”
Section: Immunostainingmentioning
confidence: 99%